Interoperable scenario simulation of land-use policy for Beijing–Tianjin–Hebei region, China. (June 2018) - Liu, Dongya; Zheng, Xinqi; Wang, Hongbin; Zhang, Chunxiao; Li, Jiayang; Lv, Yongqiang
Graphical abstract: Highlights: An extended temporal-spatial dynamics method of prediction land-use changes was proposed. The method implemented the temporal and spatial data interoperability between CA model and GIS. "Square + Circle" neighborhood of CA model was proposed to refine the neighborhood cells. We made land-use policy scenario prediction for Beijing–Tianjin–Hebei region. Abstract: In land-use change studies, scenario simulations cannot be effectively realized because of Geographic Information System (GIS) temporal-spatial interoperability bottlenecks. Based on a previous temporal-spatial dynamics method (TSDM) established by the author, this study extended the previous model and proposed an extended TSDM (ETSDM): (1) The neighborhood of cellular automata (CA) model was extended to a "Square + Circle" neighborhood, making the neighborhood more realistic and improving the simulation accuracy to a certain extent. (2) To achieve dynamic data exchange between the CA model and GIS, the scenario simulation of temporal and spatial visual interoperability from a national planning scheme or spatial location delineation to planning implementation effects can be implemented. Based on land-use data for 1995, 2005, and 2013, the simulation accuracy of the ETSDM was verified and development patterns were predicted under the following scenarios. Scenario 1 used the independent Beijing, Tianjin, and Hebei Province, and was designed as a blank control. Scenario 2 used the coordinated Beijing–Tianjin–Hebei (BTH) development area. This area was projected in order to study the probable land-use patterns in temporal and spatial dimensions under the effects of national policy data. Scenario 3 added the Xiongan New Area on the basis of Scenario 2, which was used to explore the influences of sudden land-use policies on regional land-use patterns. The results indicate that: (1) A "Square + Circle" neighborhood details the type of neighborhood cells and has an approximately 1% accuracy improvement relative to the general neighborhood rules; (2) According to the interactive operation in the model, land-use graph-number changes in the specific target region under different land-use policies can be monitored; and (3) Under different development policies, the built-up land gross of Beijing will be conserved approximately 600 km 2, along with the coordinated development of the BTH region and the establishment of the Xiongan New Area in 2030. At the same time, cropland conditions will be improved. A reason for the results may be that some of the non-capital functions will be transferred to Tianjin and Hebei Province under the national policies.